Authenticity and Verfremdung: Öyvind Fahlström’s performance Kisses Sweeter than Wine (1966) - Bäckström, Per (Sens public, 2020)
Performance art has been regarded as solidly rooted in the “Hier und Jetzt”, asserted by Walter Benjamin as the only remaining condition for the Aura. However, as Philip Auslander observes, every performance today is always already mediatized in one way or another, and still we might experience liveness and then also authenticity. Mediatization is, therefore, a (necessary) condition for authenticity. In my discussion on the Swedish artist Öyvind Fahlström’s (1928–76) performance Kisses Sweeter than Wine 1966, I nonetheless argue that not even the use of Verfremdungseffekts in avant-garde performance disrupts the construction of authenticity, even though this effect is used to attack the (presupposed) media-transparency believed to be necessary for an “authentic” experience. In his use of new technology and different broadcasting media, Fahlström was a forerunner for media art. The intermedial intricacy can be fully understood and discussed only in our own information age. His and other similar experiments in the 1960s are important links in the genealogy of today’s networked, global and multiscreen world, since they constitute early confluences of cybernetics, art and media. This is best seen in his performance, which was part of 9 Evenings. Theatre and Engineering arranged, in 1966, by Experiments in Art and Technology (E.A.T.) at the 69th Regiment Armory in New York. Fahlström mixes performance on stage with a plethora of mediated and mediatized events, which results in a show that is characterized by strong Verfremdungseffekts, yet still gives rise to an experience of authenticity.